Application of Biofertilizer on Rica Plants in Pangkalan Gelebak Village, Banyuasin Regency - Marlina, Neni; Asmawati, Asmawati; Meidelima, Dewi; Kalasari, Rastuti; Nunilahwati, Haperidah; Marlina, Marlina; Philep Rompas, Joni; Siti Aminah, Iin; Rosmiah, Rosmiah (Altifani Journal: International Journal of Community Engagement, 2021)
The farmers in Pangkalan Gelebak Village have the problem of their low agricultural productivity.  The high price of chemical fertilizers causes the ability of the population to purchase fertilizers to be deficient.  As a result, agricultural production is still far from optimal.  In addition, rice straw left alone in rice fields can become a nesting place for pests such as rats, leafhoppers, and others.  Therefore, it is necessary to transfer information on appropriate science and technology, which is environmentally friendly, to overcome the problems of farmers in Pangkalan Gelebak.  One way to overcome this is to provide counseling about the importance of processing rice straw into biofertilizers to increase production, train, guide, and practice techniques for making biofertilizers made from rice straw to increase agricultural production, especially rice, and practicing application techniques for biofertilizer made from rice straw.  Rice straw is the raw material for rice plants for farmers in Pangkalan Gelebak Village.  The method used is to make demonstration plots of rice plants organically, counseling about the importance of processing rice straw into biofertilizers to increase production, carried out from February to June 2018.  The results of using 400 kg/ha + 50 % chemical fertilizers can increase rice production from 3,5 tons/ha to 5,6 tons/ha (60,00% increase) when compared to using chemical fertilizers.